India - Organizational Transformation and Public Private Partnerships : Maharashtra State Electricity Transmission Company Limited (MSETCL) - World Bank (World Bank, 2012)
Maharashtra State Electricity Transmission Company Limited (MSETCL) was created in 2005 as a part of the unbundling exercise of the vertically integrated state power utility. The objective of this note is mainly summarizing the activities undertaken under the Technical Assistance (TA) program. This note also seeks to share the experience of Maharashtra in undertaking fast track transmission infrastructure development through a well formulated strategic alliance approach and putting in place improved business processes/organizational structures, to effectively implement this approach, with other states/stakeholders in the country. This dissemination is expected to motivate other power sector state utilities to appreciate the usefulness of the capacity building exercise as a means to bring about organizational transformation required for infrastructure scale up and to meet the market challenges arising from the current open access scenario in the power sector.